Effect Of Brand Awareness, Promotion And Ease Of Use Perceptions On Decisions To Use Linkaja E-Wallet - Aditiansa, Jovan Fitrianto; Dermawan, Rizky (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The purpose of this study is to test and know the effect of brand awareness, promotion, and perceived ease of use on the usage decisions of e-wallet LinkAja. The research method used in this study is the quantitative method. Respondents in this study were management collestudentsent of UPN “Veteran” Jawa Timur that used LinkAja. In this study, the number of samples taken as many as 94 respondents. The sampling method used non-probability sampling with the pusposive sampling technique. The data collection technics used in this study is the primary data in the form of a questionnaire which was analyzed using the Likert scale and secondary data in the form of literature. The data analysis technique used SEM-PLS. The results of this study showed that brand awareness, promotion, and perceived ease of use have a significant (positive) impact on usage decisions e-wallet LinkAja